A clinical and in-silico study exploring the association of CASP-3, NF-kB, miR-187, and miR-146 in pre-eclampsia. (2nd October 2021) - Sharma, Charu; Purohit, Purvi; Khokhar, Manoj; Modi, Anupama; Singh, Pratibha; Shekhar, Shashank; Sharma, Shailja; Gothwal, Meenakshi; Sharma, Praveen
ABSTRACT: Introduction: Apoptosis is involved in pathogenesis of Pre-eclampsia (PE), further research is needed to determine its molecular mechanism. Methods: The study recruited two groups (controls; 09, PE; 11). Biochemical tests, RT-PCR and ELISA were employed for analysis of genes and MicroRNAs (miRNA). Bioinformatics tools were employed for interactomics analysis. Results: There was increased apoptosis in maternal placental tissue (MPT) and Maternal Blood Cells (MBC) as demonstrated by expression of CASP3 and NF-κB1. miR-146-5p and 187-5p were downregulated in MBC and MPT but upregulated in fetal placental tissue (FPT).. Discussion: An increased apoptosis in MBC and MPT is a significant contributory factor for PE in pregnancy, while FPT is immune to the aforementioned effects. Graphical abstract: uf0001